Perlindungan Hukum Terhadap Pekerja Di Masa Pandemi Covid-19 - Hatane, Karina; Alfons, Saartje Sarah; Matitaputty, Merlien Irene (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Legal protection of workers in working relationships is needed, considering the position of workers socially-economically very weak especially during the pandemic covid 19. Many companies suffer losses due to restrictions on community activities that affect the company’s income, so workers and affects the normative rights of workers.Purposes of the Research: This paper ains to know the form of legal protection for workers who are laid off and know the implementation of legal protections against workers during the covid-19 pandemic.Methods of the Research: This method of research in writing uses a type of normative juridical research that examines positive legal provisions, legal principles, and legal doctrines, using approaches: statute approach and conceptual approach. The technique of collecting legal materials through literature studies and legal material analysis techniques in this study uses qualitative analysis techniques.Results of the Research: Based on the results of the study, obtained the results that the form of legal protections against workers who were laid off during the covid 19 pandemic includes 2 (two) forms of legal protection both from employers in the form of fulfillment of workers rights that have been contained in the legislation in the form of compensation and work experience latters while from the government, the issuance of legal products and worker protection programs. Implementation of such protections is applied in accordance with the regulations and circulars issued to workers during the covid 19 pandemic related to the rights fulfilled by mutual agreement although  in the context there are also workers rights that are not fully fullfiled in accordance with the provisions of the legislation until the issuance of the pre-employment card program, cash-intensive programs and social safety nets.